Desain Media Pembelajaran berbasis ICT dengan Website Google Sites pada Materi Bangun Datar untuk Siswa Kelas III Sekolah Dasar - Siregar, Dhea Aprilia Caroline; Amy, Nur Allysha Binti; Sari, Sindi Fatika (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to develop ICT-based learning media using Google Sites on flat geometry material for grade III elementary school students. The method used in this study is Research and Development (R&D) with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of the study indicate that the developed learning media is valid, practical, and effective. Based on the results of peer assessment, this media obtained a material feasibility score of 100%, language feasibility of 91.6%, and media feasibility of 91.6%, all of which are in the very feasible category. The implementation trial to 10 students showed very good results with a feasibility score of 91%, indicating that this media is effective in improving students' understanding of the concept of flat geometry. The suggestion from this study is to increase the variety of evaluation questions, especially in educational games, and expand the implementation of this media to other schools to expand its positive impact.